Patient autonomy and quality of care in telehealthcare - Rubeis, Giovanni; Schochow, Maximilian; Steger, Florian (Science and engineering ethics, 2018)
Telemedicine is a complex field including various applications and target groups. Especially telehealthcare is seen by many as a means to revolutionize medicine. It gives patients the opportunity to take charge of their own health by using self-tracking devices and allows health professionals to treat patients from a distance. To some, this means an empowerment of patient autonomy as well as an improvement in the quality of care. Others state the dangers of depersonalization of medicine and the pathologization of daily life. This paper examines the ethical implications of telehealthcare, focusing on patient autonomy and quality of care by analyzing metareviews, randomized controlled trials and narrative ethical analyses on the topic. As a result, we conclude that the technically enhanced encounter between patients and health professionals may mean an empowerment of patient autonomy when it goes along with a personal relationship based on trust, assistance and support. When it comes to the quality of care, telehealthcare may lead to an improvement as long it is adopted to the patient's individual needs.
Gesehen am 12.05.2021